2017
DOI: 10.1002/ijgo.12112
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of freeze-dried amnion graft following hysteroscopic adhesiolysis of severe intrauterine adhesions

Abstract: Use of freeze-dried amnion graft was effective in reducing IUA reformation and improving menstruation (according to pictorial blood-loss assessment chart) following hysteroscopic adhesiolysis of severe IUAs. ClinicalTrials.gov: (NCT02496052).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 25 publications
(46 reference statements)
1
49
0
Order By: Relevance
“…2), amniotic membrane treatment increased the menstrual blood volume after hysteroscopic adhesiolysis. 15,16,18 No statistically significant between-group differences were found for either measure. 15,16,18 No statistically significant between-group differences were found for either measure.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…2), amniotic membrane treatment increased the menstrual blood volume after hysteroscopic adhesiolysis. 15,16,18 No statistically significant between-group differences were found for either measure. 15,16,18 No statistically significant between-group differences were found for either measure.…”
Section: Resultsmentioning
confidence: 89%
“…No statistically significant differences in baseline data between the treatment and the control groups were reported in three studies [16][17][18] However, the fourth study showed a statistically significant difference in the etiology of intrauterine adhesions. 15,16,18 One study used a randomized controlled design but did not use allocation concealment or masking methods. Three studies adopted randomized, controlled, and masked methods, which are associated with high literature quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations